ICRISAT Hosts Training Programs for Landscape-Based Fertilizer Use in Ethiopia - Desta, Gizaw (International Crops Research Institute for the Semi-Arid Tropics, 2024)
Over 200 Participants Across 21 Districts Benefit from Hands-on Experience. The International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), under the Fertilizer Ethiopia Use Case of the CGIAR Excellence in Agronomy initiative, conducted a series of training workshops in June 2024. These sessions focused on the “Implementation Guidelines for Piloting Landscape-Based Fertilizer” across 21 districts in Amhara, Oromia, Central, and Southern Ethiopia.